Implementasi Project Based Learning untuk Mewujudkan Profil Pelajar Pancasila di Sekolah Dasar Negeri - Hidayah, Nur; Purbosari, Purwanti Pratiwi (BRILIANT: Jurnal Riset dan Konseptual, 2024)
This research aimed to analyze the implementation of Project Based Learning to create a Pancasila student profile at SD Negeri Bakulan, Yogyakarta. This type of research was qualitative in the form of a case study through interviews, observation, and document study. The research results showed good planning at SD Negeri Bakulan regarding the implementation of PjBL, which was characterized by team formation, scheduling, creating general themes, creating teaching modules, and outreach to students’s parents. The implementation stage was carried out by following the steps of the PjBL learning model. After the implementation stage, reflection and evaluation were carried out for each PjBL activity. Supporting factors in implementing PjBL at SD Negeri Bakulan include good cooperation from teachers, teacher readiness in planning and implementing it, high student enthusiasm, good parental enthusiasm, the existence of facilities and infrastructure as well as tools and materials that were readily available, and there were examples of implementing project learning on the independent teaching platform. . Meanwhile, factors that hinder the implementation were the students feeling bored in the middle of the process and teacher creativity still needs to be further developed.